Conhecimentos prévios revelados por estudantes de sexto e sétimo anos do ensino fundamental relativos à proporcionalidade - Silva, Regina Lucia da (2013)
This work aims to investigate the connections which can be established between the students previous knowledge, their hypothesis and the activity plan suggested by the professors, regarding the proportionality as a vital element to the curricular development. This topic pervades ideas that are presented in the exploring of different mathematical subjects throughout Basic Education. The investigation has a qualitative nature, is characterized as a case study and is based upon problem-situation solving by two students from a São Paulo state public school. As for the results, we highlight: the students researchers displayed the capacity to: establish relations, analyze and synthetize information, organize data targeting the resolution of the problems; they demonstrated, as well, considerable skill in natural language, good numerical abilities, being able to identify operations adequately, making use of mental or written calculations, exact or approximated. The difficulties presented related to rational numbers and to the concepts involving quantities and measurements